2021
DOI: 10.3390/microorganisms9102020
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Lactobacillus Strains Capable of Fermenting Fructo-Oligosaccharides and Inulin

Abstract: Novel probiotic strains that can ferment prebiotics are important for functional foods. The utilization of prebiotics is strain specific, so we screened 86 Lactobacillus strains and compared them to Bifidobacterium breve 2141 for the ability to grow and produce SCFA when 1% inulin or fructo-oligosaccharides (FOS) were provided as the carbon source in batch fermentations. When grown anaerobically at 32 °C, ten Lactobacillus strains grew on both prebiotic substrates (OD600 ≥ 1.2); while Lactobacillus coryniformi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 53 publications
(68 reference statements)
5
14
0
Order By: Relevance
“…Acetate production by both bifidobacteria and lactobacilli has been reported under anaerobic and glucose limiting conditions [42,43], but the level of lactate production observed in our study suggested that the bacteria may not have been stressed under the current growth conditions when compared to other studies. Lactate being the primary organic acid produced also agreed with previous results from our laboratory when lactobacilli and bifidobacteria were grown in the presence of FOS and inulin as a sole carbon source [41].…”
Section: Short Chain Fatty Acid Production By Lab Grown On Cranberry A6supporting
confidence: 90%
See 4 more Smart Citations
“…Acetate production by both bifidobacteria and lactobacilli has been reported under anaerobic and glucose limiting conditions [42,43], but the level of lactate production observed in our study suggested that the bacteria may not have been stressed under the current growth conditions when compared to other studies. Lactate being the primary organic acid produced also agreed with previous results from our laboratory when lactobacilli and bifidobacteria were grown in the presence of FOS and inulin as a sole carbon source [41].…”
Section: Short Chain Fatty Acid Production By Lab Grown On Cranberry A6supporting
confidence: 90%
“…Short chain fatty acid production was monitored for the 11 Lactobacillus strains and Bifidobacterium breve 2141, which showed optimal growth on cranberry A6 ( Figure 5 ). All strains were shown to produce predominantly lactic acid (>70 mM), which agreed with previous results from our laboratory using FOS and inulin as the sole carbon source [ 41 ], but disagreed with a previous study that reported lactate production was <10 mM for L. plantarum ATCC BAA 793 and B. longum subsp. longum UD401 when grown on cranberry xyloglucans [ 30 ].…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations